Identification and verification of ferroptosis-related genes in gastric intestinal metaplasia - Song, Biao; Li, Tingting; Zhang, Yi; Yang, Qi; Pei, Bei; Liu, Yun; Wang, Jieyu; Dong, Gang; Sun, Qin; Fan, Shanshan; Li, Xuejun (Frontiers in Genetics, 2023)
Background: Gastric intestinal metaplasia (IM) is the key link of gastric precancerous lesions. Ferroptosis is a novel form of programmed cell death. However, its impact on IM is not clear. The focus of this study is to identify and verify ferroptosis-related genes (FRGs) that may be involved in IM by bioinformatics analysis. Materials and methods: Microarray dataset GSE60427 and GSE78523 were downloaded from Gene Expression Omnibus (GEO) database to obtain differentially expressed genes (DEGs). DEGs was crossed with FRGs from FerrDb to obtain differentially expressed ferroptosis-related genes (DEFRGs). DAVID database was used for functional enrichment analysis. Protein-protein interaction (PPI) analysis and Cytoscape software were used to screen hub gene. In addition, we constructed a receiver operating characteristic curve and obtained relative mRNA expression verified by quantitative reverse-transcription polymerase chain reaction (PCR). Finally, the CIBERSORT algorithm was used to analyze the immune infiltration in IM. Results: A total of 17 DEFRGs were identified. A gene module identified by Cytoscape software was considered to be hub genes: PTGS2, HMOX1, IFNG and NOS2. ROC analysis shows that HMOX1 has good diagnostic characteristics. Immunoassay showed that the proportion of T cells regulatory (Tregs) and macrophages M0 in IM was relatively higher, while the proportion of T cells CD4 memory activated and dendritic cells activated was lower. Conclusion: We found significant associations between FRGs and IM, and HMOX1 may be diagnostic biomarkers and therapeutic targets for IM. These results may enhance our understanding of the mechanism of IM and may contribute to its treatment.